"A feeling for run and rhythm": coaches` perspectives of performance, talent, and progression in rowing - Leege, N.; Watsford, M.; Sharp, P.; O'Meara, D.; Slattery, K. (Journal of Sports Sciences, 2023)
The understanding of rowing performance has been predominantly gained through quantitative sports science-based research. In combination with this objective information, coaches` experiences may provide important contextual information for how this quantitative evidence is implemented into training programmes. The aims of this study were to (1) explore coaches` perspectives of performance indicators for competitive rowing in junior rowers, and (2) identify coaches` recommendations for developing effective technique and movement competency among junior rowers who have the potential to transition to elite competition. Twenty-seven semi-structured interviews were conducted with experienced rowing coaches through purposive sampling of an accredited coaching network. Participants` coaching experience ranged from 5 to 46 (M = 22, SD = 10) years. Data were analysed using thematic analysis. Three overarching themes were identified including, (1) getting the basics right, (2) targeting types of talent, and (3) complexities of performance. Based on these findings, sequence and boat feel, supported through the movement competency provided by hip flexibility and the trunk musculature, were considered critical for executing correct technique. Developing talent and understanding successful performance are both complex concepts when considering the individual athlete. Coaches` perspectives provided insight into key components of performance to enhance our understanding of how to better develop junior rowers.